2006
DOI: 10.1523/jneurosci.4111-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Development of Adult-Generated Granule Cells in Dentate Gyrus

Abstract: A substantial fraction of adult-generated granule cells in the dentate gyrus survive and integrate into the existing neuronal network. These newborn neurons must navigate the environment of the adult brain, a setting that is presumably less optimized for neuronal maturation compared with that in the developing brain. We used EGFP (enhanced green fluorescent protein) expression in newborn granule cells to compare the maturation of adult-generated granule cells to those generated in neonates. Labeled newborn gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 56 publications
(84 reference statements)
11
136
2
Order By: Relevance
“…In the hippocampus, the maturation of granule cells takes ~10 days during neonatal development or 3 weeks during adult neurogenesis (Overstreet-Wadiche et al, 2006). Our study found that the neuronal identity of DG cells was bi-potent during the late stages of these extended periods.…”
Section: Neuronal Phenotype Plasticity In Postmitotic Dg Cellsmentioning
confidence: 54%
“…In the hippocampus, the maturation of granule cells takes ~10 days during neonatal development or 3 weeks during adult neurogenesis (Overstreet-Wadiche et al, 2006). Our study found that the neuronal identity of DG cells was bi-potent during the late stages of these extended periods.…”
Section: Neuronal Phenotype Plasticity In Postmitotic Dg Cellsmentioning
confidence: 54%
“…Growth of both dendrites and axons of adult-born neurons occurs more slowly in the adult hippocampus (8)(9)(10). In the developing rodent brain, mossy fiber boutons reach maturity by the beginning of the third postnatal week, when the oldest granule cells in the hippocampus would be Ϸ4 weeks of age (16).…”
Section: Discussionmentioning
confidence: 99%
“…Although the existence of synaptic inputs to the dendrites of adultborn neurons has been well documented (5)(6)(7)(8)(9)(10)(11)(12), there is a lack of knowledge regarding whether and when the axons of new neurons form synaptic outputs. This makes the claim of their full integration into existing neural circuitry premature.…”
mentioning
confidence: 99%
“…Newborn GCs fire small-amplitude action potentials which may be unable to evoke transmitter release (Overstreet-Wadiche et al, 2006). We therefore examined the firing properties of GAD67-expressing GCs in juvenile G42 mice.…”
Section: Resultsmentioning
confidence: 99%